2013
DOI: 10.1099/vir.0.047472-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between nucleotide mutation and viral loads of human bocavirus 1 in hospitalized children with respiratory tract infection

Abstract: The human bocavirus 1 (HBoV1) parvovirus causes respiratory disease and primarily affects children. Despite its worldwide prevalence, the mechanisms of HBoV1 replication and pathogenesis remain largely undefined. In this study of 846 children hospitalized at the Children's Hospital of Chongqing Medical University in China for respiratory tract infection between June 2009 and May 2011, HBoV1 was detected in 112 (13.2%) by real-time quantitative PCR. The median age of HBoV1-positive patients was 10 months old. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…In agreement with others [42], the phylogenetic analysis of this study confirmed the very low degree of variability in the hBoV genomic region encoding proteins that are exposed to the virus surface and are therefore under immunologic pressure. Only 9% (62 codons) of amino acids were found to have at least one change in the VP1/VP2 gene, a finding not substantially different from that reported by Hao et al in a different geographic area [40]. In our study, several amino acid changes were observed in strains circulating in almost all the respiratory seasons.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In agreement with others [42], the phylogenetic analysis of this study confirmed the very low degree of variability in the hBoV genomic region encoding proteins that are exposed to the virus surface and are therefore under immunologic pressure. Only 9% (62 codons) of amino acids were found to have at least one change in the VP1/VP2 gene, a finding not substantially different from that reported by Hao et al in a different geographic area [40]. In our study, several amino acid changes were observed in strains circulating in almost all the respiratory seasons.…”
Section: Discussioncontrasting
confidence: 69%
“…However, mutations associated with increased or reduced replication are rarely reported for hBoV. Recently, Hao et al have reported that few nucleotide changes were correlated with a lower viral load [40]. In the present study, a double mutant (N546H and T590S) was observed in samples with a significantly higher viral load.…”
Section: Discussionsupporting
confidence: 53%
“…Amplification of HBoV1 DNA by real-time quantity PCR was performed with the NS1 primers and probe [19,20]. The plasmid amplified target fragment was cloned into the pMD19-T vector (TaKaRa Biotechonology, Dalian, China) and verified by sequencing.…”
Section: Real-time Fluorescence Quantitative Pcr For Hbov1mentioning
confidence: 99%
“…Sequence analysis showed 11 mutations among which 6 nonsense and 5 sense mutations were found in NS1 ORF (Table 1 ). We also analyzed 47 different strains from the previous reports 31 . Surprisingly, most of the mutations were located in the C-terminus of NS1 ORF; 7 sense mutations were discovered (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%